Characteristics of Maternal Mortality Cases in a Tertiary Hospital - Junita Indarti; Ferry Y Irawan (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To identify the characteristics of maternal mortality cases in a tertiary hospital in Jakarta, including socio-demographic characteristics, previous medical and obstetric history, and patient’s clinical condition on arrival at the hospital. Method: This was a survey to identify the descriptive data of maternal mortality cases through medical records during study period. Manual review of 51 medical records was conducted for 2 years from January 2013 to December 2014 in Department of Obstetrics and Gynecology, Dr. Cipto Mangunkusumo Hospital (RSCM). Result: Of 51 cases of maternal deaths, 46 subjects (90.19%) had nine years of minimum education background. There were two subjects less than 21 years old and another was 42 years old. None of these subjects were using intrauterine device (IUD) or implant as the contraceptive methods where 66.6% subjects with underlying disease never used contraception. Ninety-two percent of subjects did antenatal care (ANC) regularly and 80.4% (41 subjects) of them was done in midwives. There were 14 subjects (29.78%) who had ANC in the first trimester of pregnancy. Severe preeclampsia is the most prevalent complication in pregnancy (26 subjects, 65%), which all (100%) patients arrived at RSCM with HELLP Syndrome. Therefore, preeclampsia was the leading cause of death in RSCM. Conclusion: The characteristics of maternal death in RSCM are prevalent in the group of 25-34 years old with the high school as the educational background. Most of them are multiparity and do not use the long-term contraceptive methods. Preeclampsia is the major cause of maternal death in RSCM. Keywords: maternal mortality, risk factors, tertiary hospital